An experimental and simulation study on build thickness dependent microstructure for electron beam melted Ti-6Al-4V - Tan, Xipeng (2015)
Build thickness dependent microstructure of electron beam melted (EBM®) Ti–6Al–4V has been investigated from both experiment and simulation using four block samples with thicknesses of 1, 5, 10 and 20 mm. We observe a mixed microstructure of alternate α/β with some α′ martensite inside the 1 mm-thick sample. By contrast, only the alternate α/β microstructure with both colony and basket-weave morphologies occurs inside the 5 mm-, 10 mm- and 20 mm-thick samples. It is found that β spacing is constantly increased with the build thickness, leading to an obvious decrease in microhardness. Finite element method (FEM) simulations show that cooling rates and thermal profiles during EBM process are favorable for the formation of martensite. Moreover, full-scale FEM simulations reveal that the average temperature inside the samples is higher as the build thickness increases. It suggests that martensitic decomposition is faster in thicker samples, which is in good agreement with the experimental observations.